2006
DOI: 10.1016/j.jasms.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Using tandem mass spectrometry to predict chemical transformations of 2-pyrimidinyloxy-N-arylbenzyl amine derivatives in solution

Abstract: Tandem mass spectrometry is used to predict the chemical transformations of 2-pyrimidinyloxy-N-arylbenzyl amine derivatives. Compound 1, N-2-2-4,6-dimethoxypyrimidin-2-yloxy benzylamino phenyl benzamide was selected as a model to present our idea. The CID reactions of protonated 1 include an intramolecular S N 2 reaction and a cyclodehydration reaction. Under in-source CID conditions, deprotonated 1 undergoes a Smiles rearrangement reaction and then dissociates to the ion at m/z 349. Theoretical computations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
1
27
0
1
Order By: Relevance
“…However, gas-phase studies on PhO(CH 2 ) n O Ϫ (n ϭ 2-4) carried out by Eichinger et al [14 -16] suggested that the Smiles rearrangement can be initiated upon collisional activation without any electron-withdrawing substituents. More recently, similar rearrangement reactions were also reported by Guo et al in studies on 2-pyrimidinyloxy-N-aryl-benzylamine derivatives [9] and by Wang et al in collision-induced dissociation studies on phenoxy-N-phenylacetamide derivatives [17].…”
Section: T Tsupporting
confidence: 80%
See 2 more Smart Citations
“…However, gas-phase studies on PhO(CH 2 ) n O Ϫ (n ϭ 2-4) carried out by Eichinger et al [14 -16] suggested that the Smiles rearrangement can be initiated upon collisional activation without any electron-withdrawing substituents. More recently, similar rearrangement reactions were also reported by Guo et al in studies on 2-pyrimidinyloxy-N-aryl-benzylamine derivatives [9] and by Wang et al in collision-induced dissociation studies on phenoxy-N-phenylacetamide derivatives [17].…”
Section: T Tsupporting
confidence: 80%
“…However, deprotonated molecules of the amide compounds we were interested in may dissociate differently. As a matter of fact, it has already been reported [9] that upon collisional activation, certain deprotonated amides underwent a skeletal rearrangement before the fragmentation. A gas-phase type Smiles rearrangement mechanism was proposed to explain this rearrangement.…”
Section: T Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Here we report our studies of the gas phase chemistry of Li + adducts of these compounds upon ESI-MS/MS, and among the fragment ions we observe are those reflecting loss of LiOH. Product ions that reflect the Smiles rearrangement, which has been well documented in the solution phase [46,47] as summarized in Scheme 1, and other fragmentation reactions are also observed. To further examine the elimination of LiOH from Li + adducts of this class of amide-containing compounds, we have also studied spectra obtained from CID of [M + Li] + ions of the simpler compounds N-phenylbenzamide and N-phenylcinnamide.…”
mentioning
confidence: 69%
“…Encouragingly, DMPITC labeled peptide gave rise to a signal with 2.5-3.5 times stronger than unlabeled and PITC labeled peptides at the same molar concentration. All the priorities of DMPITC are attributed to the advanced structure, 4,6-dimethoxy-pyrimidine, which is a medium electron withdrawing group instead of phenyl in PITC [33,34]. 13 C-NMR spectra of DMPITC and PITC revealed that chemical shift of carbon atom (145.0 ppm) located in the isothiocyanate of DMPITC moved to low field with a 9.5 ppm shift compared with that of carbon atom (135.5 ppm) in PITC.…”
Section: Dmpitc: Higher Labeling Efficiency and Enhanced Sensitivitymentioning
confidence: 99%